Acute influence of loaded jump squat technique on kinetic variables in track and field athletes - Makaruk, H.; Starzak, M. (Theory and Practice of Physical Culture, 2020)
Muscle ability to generate a high amount of maximal power is of paramount importance for effectiveness across different sports. Although the jump squat is a common explosive exercise and well described in strength and conditioning literature, the issue of the technique of the consecutive jumps has been rarely discussed in the research. The present study compares the kinetic variables during the performance of the jump squat using two different jumping techniques. Ten male university semiprofessional athletes (aged 22.5±2.5 years; body weight 76.0±4.9 kg; body height 1.79±0.05 m) performed 1 set of 10 squat jumps with the barbell (20 kg) on their shoulders under two conditions in a counterbalanced order: jumps with the feet in a natural position in plantar flexion (NTO), and jumps with the feet in active dorsiflexion (ATO). The results demonstrated that the NTO created a significantly lower value of vertical force (p=0.001) when compared with the ATO condition. The NTO condition also resulted in significant (p=0.001) less peak power than the ATO. The findings suggest that the use of the jump with active dorsiflexion of the feet during the loaded jump squat may enhance the maximal force and power production.